2001
DOI: 10.1111/j.1471-0528.2001.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of intrapartum defibulation in women with female genital mutilation

Abstract: Objective To assess the use of intrapartum de®bulation for women who have had female genital mutilation.Design A retrospective case analysis. Setting King Abdulaziz University Hospital, a teaching hospital in Jeddah, Saudi Arabia.Sample Two hundred and thirty-three Sudanese and 92 Somali women who were delivered at the hospital between January 1996 and December 1999.Methods The outcome of labour of women with female genital mutilation who needed intrapartum de®bulation were compared with the outcome of labour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 9 publications
2
31
0
1
Order By: Relevance
“…An interesting finding is the lack of significant statistical differences in the first and second stages of labor between women with defibulation and women without defibulation. This is in agreement with other studies 10,21 and suggests that with timely defibulation during delivery, the duration of labor of women with female genital mutilation or cutting should not be different than women without female genital mutilation or cutting. An earlier study from Saudi Arabia showed significant prolongation in the second stage of labor between women with female genital mutilation or cutting and women without it.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…An interesting finding is the lack of significant statistical differences in the first and second stages of labor between women with defibulation and women without defibulation. This is in agreement with other studies 10,21 and suggests that with timely defibulation during delivery, the duration of labor of women with female genital mutilation or cutting should not be different than women without female genital mutilation or cutting. An earlier study from Saudi Arabia showed significant prolongation in the second stage of labor between women with female genital mutilation or cutting and women without it.…”
supporting
confidence: 92%
“…Defibulation was done as described previously. 10 After examination of the scar (Fig. 3), urinary catheterization is done.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in our study did note that "cutting" is often needed for vaginal delivery but did not mention other peripartum complications from female circumcision (Chalmers & Hashi, 2000;Vangen et al, 2004;Vangen, Stoltenberg, Johansen, Sundby, & Stray-Pedersen, 2002). There is some controversy, as other reports in the literature do not find the same complications when intrapartum defibulation is performed by knowledgeable health professionals (Essen, Sjoberg, Gudmundsson, Ostergren, & Lindqvist, 2005;Rouzi, Aljhadali, Amarin, & Abduljabbar, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Eine Studie aus Saudi-Arabien zeigt, dass zwischen infibulierten Frauen, die intrapartal deinfibuliert wurden, und unbeschnittenen Frauen kein signifikanter Unterschied hinsichtlich Apgar-Score, Blutverlust und Krankenhausaufenthalt besteht [18]. Nach Hakig [19] fällt der Apgar-Score in den ersten 10 Minuten bei Kindern unbeschnittenen Frauen günstiger aus als bei denen von beschnittenen Frauen, jedoch zeigt sich in beiden Gruppen eine gleiche Verteilung perinataler Todesfälle.…”
Section: Totgeburt Des Erstgeborenen Kindesunclassified